A study of the mediating effect of self-perceived burden between meaning in life and dignity in disabled patients based on a dignity theory model - Tang Rong; Ding Xing; Cheng Xianzong; Liu Ruian (Frontiers in Psychology)
ObjectiveTo explore the mediating role of self-perceived burden between meaning in life and the level of dignity in patients with disability.MethodsFrom July to October 2023, 229 disabled patients in a tertiary hospital in Sichuan Province, China were selected and surveyed using the Self-Perceived Burden Scale, Meaning in Life Questionnaire, and Patient Dignity Inventory.ResultsThe levels of self-perceived burden, meaning of life, and dignity of the disabled patients were 23.55 ± 9.83, 46.27 ± 9.71, and 43.38 ± 22.04 points, respectively. Self-perceived burden was positively correlated with the level of dignity (r = 0.460, p < 0.001), and meaning in life was negatively correlated with self-perceived burden and the level of dignity (r = −0.325, r = −0.526, both p < 0.001). The results of structural equation modeling showed that the total effect of the meaning in life of disabled patients on the level of dignity was −1.1945, the direct effect was −0.9559, and the indirect effect was −0.2386, with the indirect effect accounting for 19.98% of the total effect.ConclusionSelf-perceived burden partially mediated the relationship between the meaning of life and the dignity of patients with incapacitation. Caregivers should pay attention to the level of patients’ self-perceived burden and actively cooperate with treatment and control of disease development as the current goal of life to enhance patients’ meaning of life and improve the loss of dignity.